Transformações autopoieticas e a viragem teórica sistêmica estamina - Tonet, Fernando (2014)
The following article (re)constructs the autopoietic theory developed by Maturana, Varela, Luhmann and Teubner, aiming to observe the possibility of the element of stem cells acting in the autopoietic systems theory, changing totally the patterns followed so far. The theme has never been developed by social studies, only by biological sciences. In this sense, it is structured in two moments a) the autopoietic meaning in Maturana, Luhmann and Teubner; b) a new stemic approach, which alters the autopoietic knowledge developed up to date, because  an insertion of information inside the system would happen without the necessary selection, which wouldn’t mean either alopoiesis, neither insufficiency of functional differentiation. The approach method will be Niklas Luhmann’s systemic autopoietic, because it makes possible to observe the complex constitutionalism phenomena nowadays, which builds the essence of the theoretical  post-modern  thought, adding to this method new ways of observing complexities of nowadays societies.